Social Embeddedness Among Furniture Entrepreneurs In Kalijambe District Of Sragen – Central Java - Meita Indah Setyaputri; Nurhadi; Riadi Syafutra Siregar (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The concept of economic action is socially situated and embedded in all layers of actors by forming a network. Furniture business in Pilangsari Hamlet, Kalijambe Subdistrict, Sragen Regency has a main actor, namely the entrepreneur himself, and is supported by various parties in it so that it forms an embeddedness. The purpose of this research is to see the existence of the furniture business in Pilangsari Hamlet and analyze the embeddedness of furniture entrepreneurs in shaping their business and positioning their roles by looking at the relationships that exist in all the actors in it. The researcher used a qualitative method in understanding the furniture business in Pilangsari Hamlet by using a phenomenological perspective. Research data were collected through in-depth interviews and direct observation procedures, and using thematic data analysis techniques to process research data. The results showed that furniture entrepreneurs have strong social embeddedness in starting a business with family, agencies, and the surrounding environment in the motivation to open a business. Relational embeddedness is established between furniture entrepreneurs with two categories of relationships, namely trade and society, which gives rise to a culture of 'nempil' and 'jlok-jlokan'. Structural embeddedness with suppliers is divided into two categories namely local and outside, also with consumers divided into two namely users and collectors. And the added value of furniture entrepreneurs playing a role in all economic positions reinforces that economic action cannot stand alone, but requires strong social embeddedness in every step of the way.